Identification of Molecular Mechanisms Related to Pig Fatness at the Transcriptome and miRNAome Levels - Ropka-Molik, Katarzyna (Genes (Basel), 2020)
Fat deposition and growth rate are closely related to pork quality and fattening efficiency. The next-generation sequencing (NGS) approach for transcriptome and miRNAome massive parallel sequencing of adipocyte tissue was applied to search for a molecular network related to fat deposition in pigs. Pigs were represented by three breeds (Large White, Pietrain, and Hampshire) that varied in fat content within each breed. The obtained results allowed for the detection of significant enrichment of Gene Ontology (GO) terms and pathways associated directly and indirectly with fat deposition via regulation of fatty acid metabolism, fat cell differentiation, inflammatory response, and extracellular matrix (ECM) organization and disassembly. Moreover, the results showed that adipocyte tissue content strongly affected the expression of leptin and other genes related to a response to excessive feed intake. The findings indicated that modification of genes and miRNAs involved in ECM rearrangements can be essential during fat tissue growth and development in pigs. The identified molecular network within genes and miRNAs that were deregulated depending on the subcutaneous fat level are proposed as candidate factors determining adipogenesis, fatness, and selected fattening characteristics in pigs.